KANON RETORIKA PRESENTER NAJWA SHIHAB DAN PEMANFAATANNYA UNTUK PENYUSUNAN MATERI PELATIHAN PEMBAWA ACARA - Lusi Komala Sari, - (2021)
This research is based on the number of presenters who are not subject to the laws of rhetoric as signs of public speaking. In fact, being a presenter is not only about looking good and being skilled at speaking, but it should be accompanied by mastery of the art of language so that the delivery becomes charming and valuable. Therefore, an in-depth study of the rhetoric of presenter Najwa Shihab (NS) is the solution to get the theories of sanity. Based on these thoughts, this research is aimed at; (1) obtain data on the rhetorical canons of NS presenters, including; invention, arrangement, style, delivery and memory, as well as (2) to produce NS rhetoric-based presentation material designs. The main theory that forms the basis of this research is Aristotle's canon of rhetoric. Overall, this study uses a qualitative approach with a descriptive method. Data collection is done by listening to notes technique, which is done by listening to the video and then transcribing it, identifying the data, giving serial numbers to the data. To analyze the data, a content analysis technique was used whose steps were to classify the data into a data analysis format, then interpret the dominant invention, arrangement, style, delivery and memory, conclude the rhetoric of the NS presenter, and prepare the design of the presenter's training material based on the NS rhetoric. The NS rhetorical canon is unique in each of its elements. Invention is built by (1) actual, factual, and interesting topics, and (2) systematic and clear questions to expose important information that the audience should know. In the canon arrangement, NS opened the event by (1) utilizing the poetic function of language without compromising the sharpness of meaning at one time, or (2) by showing a video, conveying the content with full control, and ending the event with an aesthetic conclusion by using words that has a rhyme, thus forming a poem that is both captivating and energetic. In terms of style, NS tends to use popular diction and special diction which gives the impression of humility and equality, as well as sharpness in language. In addition, NS speech is colored by positive and direct speech strategies which have an effect on material sharpness. In terms of style, NS rhetoric is colored by repetition and ellipsis which increases the sharpness of the material and the assertiveness of the NS language. In terms of delivery, NS has vocal clarity with the right tone and speed and is not monotonous. The variety of these elements contributes greatly to the distinctiveness of NS rhetoric because it is supported by appropriate body movements, as well as eye contact and mental contact during the event. In addition, NS has a quality memory, with above average memory capabilities. Based on the peculiarities of NS's rhetoric, the presenter training materials are divided into three parts, namely about the basics of presenters, stunning presentations, and how to make the presenters exclusive. These materials have a tendency to train participants' thinking skills, so they are appropriate to be used as presenter training materials. Keywords: rhetorical canons, presenters, host, training materials